The impact of location monitoring among U.S. pretrial defendants in the district of New Jersey - Wolff, Kevin T. (Federal probation, 2017)
The article discusses the functions and powers associating to the responsibility of U.S. federal judiciary Pretrial Services System. It investigates the impact of location surveillance among American pretrial defendants in New Jersey. Also emphasized is the contribution of continued technological advancements and policy requirements in the supervision of surveillance.